KEMAMPUAN KERJA APARAT PEMERINTAH DALAM PELAYANAN KEPADA MASYARAKAT DI KANTOR CAMAT TAHUNA BARAT KABUPATEN KEPULAUAN SANGIHE - SAGHEGHE, MEITA CHRISTINA; RURU, JOORIE; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to explain the extent of the work ability of government officials in serviceto the community in the West Tahuna District Office in Sangihe Regency. This study uses qualitativeresearch, with primary and secondary data sources, then the data obtained by interview,documentation and observation. The collected data is then analyzed through data reduction and datapresentation then conclusions and verification are carried out so that they can provide answers tothe research problem. The results of this study indicate that the ability of the apparatus to provideservices to the community in the West Tahuna District of the Sangihe Islands Regency is evidentfrom intellectual abilities and physical abilities. 1. The intellectual ability of the apparatus to provideservices to the community is seen from their educational background, understanding of the rules,previous positions and support from leaders and colleagues. 2. The physical ability of the apparatusin providing services to the community is good because it is supported by the age factor of relativelyyoung employees, the ability to take advantage of new technological work facilities as well as theexistence of a good working relationship with the leadership and coworkers. And in order to improvethe ability of officials in providing services to the community in the District of West Tahuna, SangiheRegency, it is necessary to create an employee capacity development program in accordance withthe existing work. And the nature and character as an apparatus that is responsive and cares for theneeds of the community must be owned by every state civil apparatus.